Extraction of Zinc and Manganese from Alkaline and Zinc-Carbon Spent Batteries by Citric-Sulphuric Acid Solution - Francesco Ferella; Ida De Michelis; Francesca Beolchini; Valentina Innocenzi; Francesco Vegliò (International Journal of Chemical Engineering)
The paper is focused on the recovery of zinc and manganese from alkaline and zinc-carbon spent batteries. Metals are extracted by sulphuric acid leaching in the presence of citric acid as reducing agent. Leaching tests are carried out according to a 24 full factorial design, and empirical equations for Mn and Zn extraction yields are determined from experimental data as a function of pulp density, sulphuric acid concentration, temperature, and citric acid concentration. The highest values experimentally observed for extraction yields were 97% of manganese and 100% of zinc, under the following operating conditions: temperature 40∘C, pulp density 20%, sulphuric acid concentration 1.8 M, and citric acid 40 g L-1. A second series of leaching tests is also performed to derive other empirical models to predict zinc and manganese extraction. Precipitation tests, aimed both at investigating precipitation of zinc during leaching and at evaluating recovery options of zinc and manganese, show that a quantitative precipitation of zinc can be reached but a coprecipitation of nearly 30% of manganese also takes place. The achieved results allow to propose a battery recycling process based on a countercurrent reducing leaching by citric acid in sulphuric solution.